Retinal assessment in 143 patients with white matter lesions: the potential of OCTA as an evaluation tool - Zhang, Dong; Jiang, Xueying; Zhang, Yan; Qin, Jingcui (Frontiers in Neurology, 2025)
BackgroundThe retina is a simple window to reflect the changes of brain nerves. The aim of this study was to investigate the association between retinal status and white matter lesions (WMLs) in 143 patients aged 50–80 years, utilizing Optical Coherence Tomography Angiography (OCTA) and the Fazekas Visual Scale for assessment.MethodsA total of 143 subjects underwent MRI scanning to assess the degree of WMLs using the Fazekas scale. Retinal imaging was conducted utilizing OCTA. Multivariate logistic regression analysis was employed to determine the odds ratios and 95% confidence intervals associated with the Fazekas score for each factor. The relationship between cognitive function and various OCTA parameters was assessed using quadratic and cubic simulation curve models. Data following a normal distribution are presented as means, while non-normally distributed data are reported as medians. Qualitative data are expressed as percentages.ResultsAs Fazekas grades increased, ILM-IPL thickness (OR = 3.267, OR = 8.436), vessel density in the parafoveal region of the macula, retinal vessel densities (OR = 2.058, OR = 2.363), and RNFL thickness significantly reduced (p < 0.05). With increasing Fazekas scores, the bilateral foveal avascular zone showed a significant increase (OR = 0.362, OR = 0.458) (p < 0.05). Retinal thickness and vascular density were negatively correlated with WMLs, and positively correlated with cognitive function (p < 0.05).ConclusionThe severity of WMLs increases as retinal thickness and vascular density decrease. OCTA examination has a degree of role in screening for WMLs caused by cerebral microvascular disease. Its effectiveness in screening early asymptomatic individuals or those with mild cognitive impairment is somewhat limited.